Selection and Use of Engineering Materials. - Crane, F. A. A.
The aim of this book is to provide an understanding of the basic principles of materials selection as practised in engineering manufacture and design with an overview of established materials usage. Emphasis is placed on identifying service requirements and how materials relate to those requirements, rather than listing materials and describing applications. This edition has been revised throughout and now includes coverage of the use of new materials in engineering, materials for bearings and tribological usage, and the use of materials in civil engineering structures. It has also been expand.